Application Of Complementary Therapy With Fenugreek Seed Tea (Klabet) To Increase Breast Milk Production In Langkapura District, Bandar Lampung City, 2023 - Mega Silfia Sari; Ninik Indayani (CV. Inara, 2024)
Background: Exclusive breastfeeding coverage in Indonesia in 2019-2020 decreased from 67.74% to 56.9%. This is caused by several problems, both maternal and baby problems. Babies who are not exclusively breastfed are very susceptible to diseases such as respiratory tract infections (ARI), diarrhea, severe intestinal problems in premature babies, decreased Intelligence Quotient (IQ) (Wijayanti, 2015). Therefore the author is interested in conducting research on